2015
DOI: 10.1037/neu0000137
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visual statistical learning in adults with autism.

Abstract: Individuals with autism spectrum disorder (ASD) are often characterized as having social engagement and language deficiencies, but a sparing of visuo-spatial processing and short-term memory, with some evidence of supra-normal levels of performance in these domains. The present study expanded on this evidence by investigating the observational learning of visuospatial concepts from patterns of covariation across multiple exemplars. Child and adult participants with ASD, and age-matched control participants, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 76 publications
(139 reference statements)
4
47
3
2
Order By: Relevance
“…A recent study by Spanò, Peterson, Nadel, Rhoads, and Edgin (2015) convincingly showed that children with ASD use both low-level priors (on convexity and surface integration) and higher level priors (based on form/ object memories) in a basic visual figure-ground segregation task, to the same extent as typically developing children. As pointed out before, even probabilistic and implicit regularities can be learned in ASD (e.g., Nemeth et al, 2010;Roser, Aslin, McKenzie, Zahra, & Fiser, 2015;Solomon, Smith, Frank, Ly, & Carter, 2011). If the task makes clear which stimuli or dimensions are relevant, people with ASD may even be more sensitive to changes in environmental patterns (Westerfield, Zinni, Vo, & Townsend, 2015) as seen in the P3 ERP component, consistent with our proposal of increased precision of prediction errors.…”
Section: Introductionsupporting
confidence: 88%
“…A recent study by Spanò, Peterson, Nadel, Rhoads, and Edgin (2015) convincingly showed that children with ASD use both low-level priors (on convexity and surface integration) and higher level priors (based on form/ object memories) in a basic visual figure-ground segregation task, to the same extent as typically developing children. As pointed out before, even probabilistic and implicit regularities can be learned in ASD (e.g., Nemeth et al, 2010;Roser, Aslin, McKenzie, Zahra, & Fiser, 2015;Solomon, Smith, Frank, Ly, & Carter, 2011). If the task makes clear which stimuli or dimensions are relevant, people with ASD may even be more sensitive to changes in environmental patterns (Westerfield, Zinni, Vo, & Townsend, 2015) as seen in the P3 ERP component, consistent with our proposal of increased precision of prediction errors.…”
Section: Introductionsupporting
confidence: 88%
“…The findings reported by Roser et al [62] revealed intact SL in individuals with ASD-as well as a somewhat surprising finding of superior SL in adults with ASD by comparison with a control group of adults. Superior SL in individuals with ASD was not observed in the child data.…”
Section: Autism and Statistical Learningmentioning
confidence: 82%
“…Departing from a focus on sequential SL in many of the other studies in this area, Roser and co-workers examined the detection of spatial regularities in those with and without ASD [62]. If SL is comprised of multiple components, it is reasonable to expect that (at least some of) these components process spatial regularities differently from sequential regularities.…”
Section: Autism and Statistical Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, encoding while making this form of judgment may have contributed less effectively to the otherwise typical deep encoding found in individuals with ASD (Toichi and Kamio, 2002; Mottron et al, 2001). Findings of intact recognition of items encoded relationally, on the other hand, suggests that those with ASD were relatively better at recognizing items under conditions involving their strong visuospatial information processing abilities (Joseph et al, 2005; Roser et al, 2015; Caron et al, 2006). We are not the first to observe that stimulus characteristics influence how effectively items can be encoded (Gaigg et al, 2008).…”
Section: Discussionmentioning
confidence: 99%